2016
DOI: 10.1155/2016/7654234
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Relationship between the P-Wave Velocity and the Mechanical Properties of Damaged Sandstone

Abstract: To obtain an improved and more accurate understanding of the relationship between the P-wave velocity and the mechanical properties of damaged sandstone, uniaxial compression tests were performed on sandstone subjected to different high-temperature treatments or freeze-thaw (F-T) cycles. After high-temperature treatment, the tests showed a generally positive relationship between the P-wave velocity and mechanical characteristics, although there were many exceptions. The mechanical properties showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Though the applications of PIs are diverse, they are still confined to the laboratory and far away from commercialization. PIs are formed from anhydride and amine polycondensations [ 17 ]. PIs have been in development since their introduction in 1955.…”
Section: Introductionmentioning
confidence: 99%
“…Though the applications of PIs are diverse, they are still confined to the laboratory and far away from commercialization. PIs are formed from anhydride and amine polycondensations [ 17 ]. PIs have been in development since their introduction in 1955.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of wave velocity characteristics of rock, Charalampos saroglou studied the influence of the granite fracture degree on P-wave and S-wave velocity [17]. Q. Ding studied the relationship between P-wave velocity and mechanical properties of sandstone treated by a high temperature and freeze-thaw cycle [18]. L. Yang studied the evolution law of acoustic spectrum parameters of granite in the process of uniaxial compression loading failure, and found that, when the shear wave shifts from the broadband multimodal state to the low-frequency unimodal state, it means that the rock sample is about to be destroyed [19].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic testing is convenient and rapid and is commonly used to study anisotropy in rocks. The ultrasonic wave velocity is well correlated with the mechanical parameters of rocks [18][19][20]. Ultrasonic testing has been used to study anisotropic changes in rock under different load conditions, such as fatigue load [17,21], impact load [22] and static load [23], and under different environmental conditions, such as high temperatures [24], freeze-thaw cycling [25] and dry-wet cycling [26].…”
Section: Introductionmentioning
confidence: 99%